« Remember Paoli ! » : Que reste-t-il de Paoli dans la mémoire américaine ? - Marcandria Peraut (XVII-XVIII)
In 1755, General Pasquale Paoli brought to a head the Corsican revolution that had begun a quarter of a century earlier. Unable to quell the revolt, the Republic of Genoa, to which the island had belonged for five centuries, enlisted the help of its ally Louis XV. After freeing himself from the former, Paoli led the resistance against the latter. In North America, stories of his resistance captivated the “Sons of Liberty” to such an extent that the island general became a symbol across the Atlantic: “the champion of liberty”. This paper looks at how the political use of the “Father of the Corsican homeland” transcended the American imagination during the revolutionary period. The second part of the paper focusses on the metamorphosis of the Paolian memory in the United States from the eighteenth to the nineteenth century. It then identifies the memorial markers instituted on the American soil that ensured the transmission of the Paolian memory from the eighteenth century to the present day.